Ownership of Residential Rental Property in Regional Housing Markets - Andrew Narwold (European Regional Science Association (ERSA), 2004)
Previous studies have demonstrated the role that income tax incentives to landlords play in the determination of market rental rates. Landlords typically receive benefits from accelerated depreciation on real assets that are usually appreciating. The value of this tax benefit depends both on the depreciation schedule as well as the landlord's marginal tax rate. Changes in income tax law in the 1980's dramatically affected both of these factors. In 1980, the top federal marginal tax rate was 70%, and rental housing could be depreciated on a double-declining balance over 20 years. The Economic Recovery Tax Act of 1980 reduced the top marginal tax rate significantly. Changes were made in 1984 that altered the depreciation schedule so that rental property could be depreciated more rapidly. The Tax Reform Act of 1986 reformed the depreciation schedule so that rental property had to be depreciated over 27 years: a significant change for landlords. In addition, the top federal marginal tax rate was reduced to 33 percent. The main direction of the changes in the federal tax code in the 1980's was to decrease the tax advantages associated with rental property. Decreases in the top marginal tax rate reduced the value of tax write-offs, while increases in the length of time required for depreciation reduced the amount of depreciation taken each year. This paper examines the impact that these changes had on the rental housing market by looking at the changes in the relative cost of renting over the years 1986-1990.
Keywords: 330